2014
DOI: 10.1021/jp504055j
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Properties of Electrodeposited Sn Anodes for Na-Ion Batteries

Abstract: The electrochemical properties and sodiation/desodiation mechanism of Sn electrodes prepared by electrodeposition were investigated for Na-ion batteries. The sodiation of the electrodeposited Sn electrodes proceeded via three conjugated reactions in the cutoff voltage range of 0.001–0.65 V, as follows: the β-Sn phase, which contains a small amount of Na, was sodiated into amorphous NaSn, and crystalline Na9Sn4 and Na15Sn4 were then formed sequentially. However, the cycle performance of the electrode was highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 35 publications
2
42
0
Order By: Relevance
“…As shown in Figure 6(c), the first charge curve for the Sn nanofibers has three distinct plateaus, denoted as I, II and III in order of increasing Na content. On the basis of the results of the previous study, 24 it can be suggested that the electrochemical sodiation/ desodiation of the Sn nanofibers undergoes the following reactions in the voltage range of 0.001 to 0.650 V.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…As shown in Figure 6(c), the first charge curve for the Sn nanofibers has three distinct plateaus, denoted as I, II and III in order of increasing Na content. On the basis of the results of the previous study, 24 it can be suggested that the electrochemical sodiation/ desodiation of the Sn nanofibers undergoes the following reactions in the voltage range of 0.001 to 0.650 V.…”
Section: Resultsmentioning
confidence: 91%
“…49,50 However, pure Sn electrodes exhibit poor cyclability on account of the structural failure of Sn that results from a significant volume change (up to approximately 420%) during sodiation/desodiation. 24 Consequently, major challenges remain for improving the cycle stability of the Sn electrodes. One possible strategy for overcoming such a problem is to make a nanostructured or nanoscale electrode for facilitating the relaxation of material stress.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…24 The cell consisted of the Sb/Sb 2 O 3 electrode as a working electrode, pure Na(SigmaAldrich) as a counter electrode, and 1 M NaClO 4 (Sigma-Aldrich) dissolved in anhydrous over the potential range of 0.01 ~ 2.50 V vs. Na + /Na at 25 °C. For rate capability testing, the charge and discharge currents were varied from 66 to 3300 mA g -1 and returned to 66 mA g -1 .…”
Section: Introductionmentioning
confidence: 99%